The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.cell.2015.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of AMPK by a Cancer-Specific Ubiquitin Ligase

Abstract: SUMMARY AMP-activated protein kinase (AMPK) is a master sensor and regulator of cellular energy status. Upon metabolic stress, AMPK suppresses anabolic and promotes catabolic processes to regain energy homeostasis. Cancer cells can occasionally suppress the growth restrictive AMPK pathway by mutation of an upstream regulatory kinase. Here, we describe a widespread mechanism to suppress AMPK through its ubiquitination and degradation by the cancer-specific MAGE-A3/6-TRIM28 ubiquitin ligase. MAGE-A3 and MAGE-A6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
333
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(366 citation statements)
references
References 63 publications
13
333
1
3
Order By: Relevance
“…The concept of platforms for assembly of autophagic machinery in mammalian cells also extends to generic, starvation-induced autophagy, which utilizes exocyst components specifically endowed with Exo84 (Bodemann et al, 2011). However, TRIM engagement with autophagy may entail other mechanisms, as for example TRIM28 has multiple (both positive and negative) proposed mechanisms of action (Barde et al, 2013;Yang et al, 2013;Pineda et al, 2015), whereas the mechanism of autophagy induction for TRIM13 in response to the ER stress has not been fully delineated (Tomar et al, 2012), although it shows a relationship with p62 and DFCP, an ER-derived autophagy precursor compartment termed omegasome (Axe et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of platforms for assembly of autophagic machinery in mammalian cells also extends to generic, starvation-induced autophagy, which utilizes exocyst components specifically endowed with Exo84 (Bodemann et al, 2011). However, TRIM engagement with autophagy may entail other mechanisms, as for example TRIM28 has multiple (both positive and negative) proposed mechanisms of action (Barde et al, 2013;Yang et al, 2013;Pineda et al, 2015), whereas the mechanism of autophagy induction for TRIM13 in response to the ER stress has not been fully delineated (Tomar et al, 2012), although it shows a relationship with p62 and DFCP, an ER-derived autophagy precursor compartment termed omegasome (Axe et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ induces autophagy (Inbal et al, 2002;Gutierrez et al, 2004;Fabri et al, 2011) and influences cytokine networks and polarization of immune systems (Ghezzi and Dinarello, 1988;Schroder and Tschopp, 2010;Mishra et al, 2013), whereas TRIMs are involved in immune responses (Kawai and Akira, 2011) and, through an assortment of proposed mechanisms affect autophagy (Niida et al, 2010;Tomar et al, 2012;Barde et al, 2013;Pizon et al, 2013;Yang et al, 2013;Khan et al, 2014;Mandell et al, 2014;Pineda et al, 2015). IFN-γ can induce expression of a subset of TRIMs (Carthagena et al, 2009).…”
Section: Trims Participate In Ifn-γ-induced Autophagymentioning
confidence: 99%
“…TRIMs affect autophagy as a whole process (Lipinski et al, 2010;Perera et al, 2011;McKnight et al, 2012;Tomar et al, 2012;Barde et al, 2013;Pizon et al, 2013;Khan et al, 2014;Pineda et al, 2015) and interact with ATG factors (Behrends et al, 2010;Yang et al, 2013;Mandell et al, 2014;Kimura et al, 2015). Of the 82 human TRIMs, 49 TRIMs have an effect on autophagy (Table S1).…”
Section: Trims As Autophagy Regulatorsmentioning
confidence: 99%
“…Several genome-wide screens, albeit not aimed at studying TRIMs, indicate that a number of additional TRIMs (TRIM29, TRIM51 and TRIM69) modulate autophagy (Lipinski et al, 2010;McKnight et al, 2012). Furthermore, TRIM13, TRIM28, TRIM55, TRIM56 and TRIM63 have been reported in separate studies to affect autophagy (Tomar et al, 2012;Barde et al, 2013;Pizon et al, 2013;Yang et al, 2013;Khan et al, 2014;Kimura et al, 2015;Pineda et al, 2015).…”
Section: Trims As Autophagy Regulatorsmentioning
confidence: 99%
“…Pineda et al (2015) reported that the melanoma antigens MAGE-A3/-A6 recruit the ubiquitin ligase TRIM28 to AMPK-α1 and triggers its degradation. MAGE-A3/-A6 are closely related tumour antigens that are normally only expressed in testis, but are aberrantly re-expressed in some tumors.…”
Section: Grahame Hardiementioning
confidence: 99%